History and modernity of the economy of railway transport in the works of VNIIZHT scientists - L. A. Mazo; O. F. Miroshnichenko; E. N. Efimova (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
The article reflects the most important areas of work and the contribution of scientists of the Department of Economics and Finance of the JSC “VNIIZHT” (now the scientific center “Economics of Complex Projects and Tariff Formation”) in the development of economic science in railway transport since the foundation of the department in 1944 to the present.Theoretical foundations for measuring the economic efficiency of capital investments and new technology in the national economy were created by the head of the department academician T. S. Khachaturov, and then adapted to the conditions of railway transport by the head of the department Dr. Tech. Sci., prof. A. E. Gibshman, head of the sector Dr. Econ. Sci., prof. N. N. Barkov and their followers. Issues of management accounting, analysis, planning of operating costs, calculating the cost of transportation, calculating the unit costs of measuring transport work are central to the research of the department. Under the scientific guidance of Dr. Econ. Sci., prof. A. P. Abramov in this area of research in the department has developed a large scientific school. In the development of scientific areas for economic incentives and increasing labor productivity and financial management, a great contribution was made by Dr. Econ. Sci., prof. M. M. Tolkacheva. Traditional scientific direction for the department of economics is the improvement of pricing for freight and passenger transportation, and other activities. Theoretical research and practical development since the beginning of the 70s of the last century were conducted under the leadership of Dr. Econ. Sci. A. V. Kreinin, and later — the head of the department Dr. Econ. Sci. L. A. Mazo. Since the mid-80s under the direction of Dr. Econ. Sci., prof. O. F. Miroshnichenko, the issues of the economy of passenger transportation stand out in a separate scientific direction, covering high-speed traffic, costs, marketing, tariffs, reforming the passenger complex.At present, the staff of the research center continues to conduct research in the most important areas of the economy of railway transport, which contribute to the increase in the efficiency and competitiveness of Russian Railways in the transport services market.